Asynchronous Learning Experiences for Visually Impaired Students: Exploring Processes and Challenges - Fatimatuzzahra, Ana; Khoirunnisa, Chintia; Meiyani, Neni; Sensus, Agus Irawan; Qurrotullain, Aini (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
Asynchronous learning facilitates students' convenient access to learning materials and enables them to engage with each other at their preferred pace. This type of learning, characterized by its lack of time constraints, grants students the freedom to acquire knowledge whenever they deem ﬁt. Regrettably, visually impaired students have not been able to fully beneﬁt from the widespread adoption of asynchronous learning, despite its proven eﬀectiveness for diverse groups in gaining both academic knowledge and practical skills through LMS-based platforms. Consequently, this study endeavors to uncover the processes, obstacles, and educational experiences encountered by visually impaired students in the application of LMS-based asynchronous learning. The research employs a qualitative method, relying on in-depth interviews to gather comprehensive information. The collected data is subsequently transcribed, categorized, and carefully analyzed to derive conclusive study outcomes. The results reveal the speciﬁc requirements of visually impaired students in asynchronous learning via LMS, highlighting challenges such as comprehending video presentations, limited teacher interaction, accessibility issues, and incompatible reading formats.